Cost performance for building construction projects in Klang Valley - A.S. Ali,; S.N. Kamaruzzaman, (Penerbit UKM, 2010)
Since seventies, the economic of Malaysia has undergone rapid growth. Construction industry constitutes an important element of Malaysian economy. It shows how important to control and manage the projects in good quality and efficiently. There are four fundamental constraints needed to be considered when managing the construction projects, which are scope, cost, time, and quality. In order to manage the projects successfully, it is necessary to consider whether the project is within those four constraints. However, it found that there were many problems on cost performance in many countries. One of the major problems was cost overrun in construction projects. In Malaysia, the problem of cost overrun considered significance in construction industry. There were many factors that contribute to cost overrun in Malaysian construction projects. The factors might become risks and lead to negative effect to the projects. Hence, this research is to identify factors that contribute to cost overrun and potential measures to overcome the problem with the focus given to construction projects within Klang Valley. The method used in this research is quantitative based. A questionnaire survey conducted to collect data from the respondents that consisted of project manager, quantity surveyor, M & E Engineer, C & S Engineer, and other related respondents. Questionnaires were distributed to 30 respondents from construction firms in Klang Valley. Data collected form a database for analysis using Statistic Package for Social Sciences (SPSS) version 17.0. Descriptive statistics and ranking analysis were used in data analysis. The result shown that the most serious factor contributes to cost overrun was inaccurate or poor estimation of original cost and the factor do not affect most was mistake in design. The most important method to control construction cost is proper project costing and financing. On the other hand, the least important approach was establishing a system in design. In conclusion, the problem of cost overrun is not a small issue but could cause serious problems to the construction industry in Malaysia.